Mediation Efforts in Domestic Violence Cases at the Lubuk Linggau City Police Department, Reviewed from Islamic Law and Positive Law - Jumino; Rifanto Bin Ridwan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Domestic Violence (DV) constitutes a serious social and legal issue in Indonesia. Domestic violence not only inflicts physical and psychological harm on victims but also undermines the harmony of the household as a fundamental social institution within society. According to Article 1 of Law Number 23 of 2004 concerning the Elimination of Domestic Violence, domestic violence is defined as any act against an individual, particularly a woman, that results in physical, sexual, psychological suffering, and/or household neglect.This study employs an empirical juridical (sociological) legal research method, combined with a normative juridical approach. This methodological combination is chosen because the research not only analyzes the applicable written legal regulations (positive law and Islamic law) but also examines how these laws are implemented in practice, specifically in the mediation processes of domestic violence cases within the jurisdiction of the Lubuk Linggau City Police Department.The mediation process in domestic violence cases at the Lubuk Linggau City Police demonstrates a recurring pattern of non-litigation dispute resolution, often pursued under the pretext of familial considerations or social pressure. From the perspective of Islamic law, mediation in domestic conflicts is principally permissible for the purpose of reconciliation and public interest (maslahah), as stipulated in the Qur'an and the practices of the Prophet’s companions. However, Islam also emphasizes the protection of life, dignity, and justice—principles that are integral to the objectives of Islamic law (maqāṣid al-sharī‘ah). From the standpoint of positive law, mediation in domestic violence cases is normatively restricted and cannot serve as grounds to terminate legal proceedings. Law Number 23 of 2004, the Chief of Police Regulation Number 8 of 2021, and the Attorney General’s Regulation Number 15 of 2020 explicitly limit the application of restorative justice, particularly in cases involving repeated violence, serious physical injury, or offenses against vulnerable groups.